2018
DOI: 10.4038/jnsfsr.v46i3.8484
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry as a tool in species identification: a study with special reference to species of the genus Mycalesis (Lepidoptera: Nymphalidae)

Abstract: Morphological variability among four species of Mycalesis in Sri Lanka that are difficult to discriminate due to their morphological similarity was investigated to identify characters that distinguish species more accurately. Using traditional morphometrics, 90 variables from the wing, forelegs and genitalia of M. perseus typhlus, M. mineus polydecta, M. subdita and M. rama were measured and analysed. A set of 19 characters of the wing, male genitalia and forelegs were identified to discriminate species. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…These points meet the criteria of Zelditch et al (2012) for landmark selection, being easy to identify, morphologically significant, lying in the same plane, conserved in all individuals and providing an adequate coverage of the morphological structure to be quantified. Landmarks at the origin and end of veins have been commonly used in morphometric studies on insects (Dworkin & Gibson, 2006;Breuker et al, 2010;Bai et al, 2016;Goonesekera et al, 2018). We digitized 17 landmarks on the forewing (FW) on specimens of both genera (Figure S4) using tpsdig v. 2.…”
Section: Morphometricsmentioning
confidence: 99%
“…These points meet the criteria of Zelditch et al (2012) for landmark selection, being easy to identify, morphologically significant, lying in the same plane, conserved in all individuals and providing an adequate coverage of the morphological structure to be quantified. Landmarks at the origin and end of veins have been commonly used in morphometric studies on insects (Dworkin & Gibson, 2006;Breuker et al, 2010;Bai et al, 2016;Goonesekera et al, 2018). We digitized 17 landmarks on the forewing (FW) on specimens of both genera (Figure S4) using tpsdig v. 2.…”
Section: Morphometricsmentioning
confidence: 99%
“…In addition, detailed forewing morphometrics confirmed morphological differences between the two species. Using morphometrics, several authors have already shown that wing characteristics can serve as useful traits for delimitating Lepidoptera species [ 7 , 8 , 10 , 11 ]. Here, we confirmed the usefulness of morphometric analysis of forewings as important for species identification and classification.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of SEM is that it gives us more detailed insights into morphology and provides much new information that is not available with traditional morphological examination [ 6 ]. Wings are highly heritable structures and thus are suitable for morphometric studies in lepidopterans [ 7 , 8 , 9 , 10 , 11 , 12 ]. The majority of modern phylogenetic studies widely rely on the mitochondrial cytochrome c oxidase subunit I gene (COI) for species delimitation in animals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In butterflies, cases of morphologically similar species that are difficult to identify are common, and traditional morphometry or geometric morphometry has been used to reliably aid in their identification [26][27][28] . The present study was conducted on the morphometric analysis of Melanitis phedima (Cramer, 1780) belonging to the family Nymphalidae, and due to a dearth of literature data on this butterfly, present findings were compared with the following findings: Akand et al [15] on Lycaenidae, Mahdi et al [16][17] , on Lycaenidae and Pieridae, Dhungel and Otaki [29] on Nymphalidae, Roy et al [30] , Goonesekera et al [31] , and Wells et al [32] on Nymphalidae. In this study, the average body length of M. phedima was recorded as 22.02±1.45 mm, while the mean body length was 16.10 2.55 mm in Eurema hecabe (L.), 9.942±0.98 mm in Chilades pandava, 9.116±0.42 mm in Chilades lajus was recorded by Mahdi et al [16][17] .…”
Section: Discussionmentioning
confidence: 99%